Roman portable sundials : the empire in your hand - Talbert, Richard J. A. (Oxford University Press, 2017)
Talbert investigates miniature sundials which can be adjusted for the owner's whereabouts. They incorporate a list of locations and latitudes for ready reference, data that offers insight into Romans' worldviews. To some perhaps, these sundials were primarily symbols of scientific awareness as well as imperial mastery of time and space